ABSES OTAK ASPERGILUS PADA PASIEN IMUNOKOMPETEN : SEBUAH LAPORAN KASUS JARANG - Maria Gabriella Sainlia (PERDOSNI, 2022)
Background Central nervous system (CNS) Aspergillosis is a common entity in the last few decades, particularly in immunocompromised population and also following covid-19 infection. As this finding is uncommon and present with atypical symptoms in immunocompetent patient, it is frequently misdiagnosed as tumor or bacterial abscess. Despite difficult diagnosis, challenges in starting and maintaining treatment also complicates patients management. Case A 36 years old, HIV negative, presented with progressive headache and blurry vision for 6 months. Initial brain MRI showed multiple lesion in bilateral frontal lobes with diffuse oedema, suggestive malignancy. Craniotomy removal tumor was performed and yield results of aspergillus sp. from brain tissue histo-pathology. Intravenous Voriconazole was administered for two weeks followed by oral itraconazole for six months. Clinical improvement was seen following antifungal treatment, and patient can return to normal activities on 6-months follow up. Conclusion Aspergillosis brain abscess is rare in immunocompetent host, and often considered as other diagnosis. Aside from surgical procedures, long-term antifungal medication also part of backbone treatment to eradicate infections. Early suspicion and awareness of CNS invasive fungal infection are key to desired outcome. Keywords: Aspergillus, central nervous system infection, antifungal